Carbonaceous aerosols in megacity Xi'an, China: Implications of thermal/optical protocols comparison. (May 2016) - Han, Y.M.; Chen, L.-W.A.; Huang, R.-J.; Chow, J.C.; Watson, J.G.; Ni, H.Y.; Liu, S.X.; Fung, K.K.; Shen, Z.X.; Wei, C.; Wang, Q.Y.; Tian, J.; et al.
Abstract: Carbonaceous aerosol is an important component that influences the environment, climate, and human health. Organic and elemental carbon (OC and EC) are the two main constituents of carbonaceous aerosols that have opposite, i.e., cooling versus warming, effects on the Earth's radiation balance. Knowledge on the variability of OC/EC splits measured by different thermal/optical protocols is useful for understanding the uncertainty in the climate models. This study shows good correlations within OC or EC (r 2  > 0.83, P < 0.001) across the IMPROVE, IMPROVE_A, and EUSAAR_2 protocols for both ambient aerosol samples and biomass burning samples. However, EC concentrations differ by more than two folds, and OC/EC ratios differ up to a factor of 2.7. The discrepancies were attributed to the selection between the reflectance and transmittance corrections and the different peak inert-atmosphere temperature. The IMPROVE and IMPROVE_A protocols also quantified different char and soot concentrations, two subtypes of EC with distinct chemical and optical properties. Char, but not soot, was found to correlate with the humic-like substances (HULIS) content in the samples, suggesting that both char and HULIS originate mainly from biomass burning. A one-year (2012–2013) ambient aerosol monitoring in Xi'an, China, shows that OC, EC, and char displayed winter highs and summer lows, while soot had no seasonal trend. The char/soot ratios showed a "single peak" in winter, while OC/EC ratios exhibited "dual peak" feature due to the influence of secondary organic aerosol formation. In addition to commonly measured OC and EC, we recommend both char and soot from a common reference method to be considered in the chemical transport and climate models. Graphical abstract: Highlights: OC/EC split ratio is a key to evaluate the cooling versus warming effects of aerosols. Over twofold difference in EC concentrations and OC/EC ratios by different protocols. Good correlations between char and HULIS-C suggest common sources, likely the widespread biomass burning in the region. Char/soot ratios contrast OC/EC ratios in seasonal variation. Char and soot should be considered in chemical transport and climate models.